The Relationship Between Family Support and Teenage Activity in Youth Integrated Service post in Purwosari District, Surakarta - Adelia Saputri; Kusuma Estu Wardani (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Adolescence is a transition period from childhood to adulthood where a person experiences significant biological, psychological, and social changes. This development encourages more mature behaviors in adolescents related to various adolescent health problems, thus requiring comprehensive and integrated services that include all elements of different programs and sectors, such as the development of adolescent care health services in the form of an Adolescent Integrated Service Post. This study aimed to determine the relationship between family support and adolescents' activity in adolescent integrated service posts in Purwosari district, Surakarta, Central Java. This study is a quantitative study with a cross sectional design. This research was conducted from October to December 2023 in Purwosari Village, Laweyan District, Surakarta. The total population was 818 adolescents aged 15-19 years. The research sample was 80 adolescents selected by snowball sampling technique. The research instrument used a questionnaire. The research data were analyzed univariately and bivariately (chi-square test). The results showed a p-value = 0.028, which means that there is a relationship between family support and adolescents' activeness at the integrated youth service post in Purwosari Village. Recommendations given to the health department to improve the implementation of integrated service post activities aimed at adolescents so that it can run optimally and more often conduct activities that can arouse the interest of adolescents who do not participate in youth activities, as well as appeal to parents to encourage the younger generation to start actively participating in youth integrated service post activities. Keywords: Family Support, Adolescent Activities, Youth Integrated Service Post